Age-related changes in mice behavior and the contribution of lipocalin-2 - Ferreira, Ana Catarina; Sousa, Nuno; Sousa, João Carlos; Marques, Fernanda (Frontiers in Aging Neuroscience, 2023)
Aging causes considerable changes in the nervous system, inducing progressive and long-lasting loss of physiological integrity and synaptic plasticity, leading to impaired brain functioning. These age-related changes quite often culminate in behavioral dysfunctions, such as impaired cognition, which can ultimately result in various forms of neurodegenerative disorders. Still, little is known regarding the effects of aging on behaviour. Moreover, the identification of factors involved in regenerative plasticity, in both the young and aged brain, is scarce but crucial from a regenerative point of view and for our understanding on the mechanisms that control the process of normal aging. Recently, we have identified the iron-trafficking protein lipocalin-2 (LCN2) as novel regulator of animal behaviour and neuronal plasticity in the young adult brain. On the other hand, others have proposed LCN2 as a biological marker for disease progression in neurodegenerative disorders such as Alzheimer’s disease and multiple sclerosis. Still, and even though LCN2 is well accepted as a regulator of neural processes in the healthy and diseased brain, its contribution in the process of normal aging is not known. Here, we performed a broad analysis on the effects of aging in mice behaviour, from young adulthood to middle and late ages (2-, 12- and 18-months of age), and in the absence of LCN2. Significant behavioral differences between aging groups were observed in all the dimensions analyzed and, in mice deficient in LCN2, aging mainly reduced anxiety, while sustained depressive-like behaviour observed at younger ages. These behavioral changes imposed by age were further accompanied by a significant decrease in cell survival and neuronal differentiation at the hippocampus. Our results provide insights into the role of LCN2 in the neurobiological processes underlying brain function and behaviour attributed to age-related changes.